Analysis of gut and circulating microbiota characteristics in patients with liver cirrhosis and portal vein thrombosis - Ping Qi; Ping Qi; Xu-xu Yang; Xu-xu Yang; Cun-kai Wang; Wei Sang; Wei Zhang; Yun Bai (Frontiers in Microbiology)
BackgroundPortal vein thrombosis (PVT) is a common and serious complication of liver cirrhosis, often associated with worsened prognosis and increased risk of hepatic decompensation. The role of gut and circulating microbiota in its pathogenesis remains unclear.MethodsWe enrolled cirrhotic patients with PVT (n = 17) and cirrhotic patients without PVT (n = 25). Fecal and peripheral blood samples were collected from all; portal vein samples were obtained from 16 patients undergoing TIPS. 16S rRNA sequencing was performed on fecal, peripheral blood, and portal venous blood samples to compare the diversity, structural differences, key microbial taxa, and characteristic variations of gut and circulating microbiota between cirrhotic patients with and without PVT.Results(1) Gut microbiota showed no α-diversity difference between groups, but β-diversity differed significantly. PVT patients had increased Gram-negative bacteria (such as Escherichia-Shigella) and decreased SCFA-producing taxa. (2) Compared with peripheral vein microbiota, portal vein microbiota showed significant difference in α diversity and β diversity in cirrhotic patients with PVT, with Massilia enriched. (3) Portal microbiota had the highest diagnostic value for PVT (AUC = 0.95). (4) The tPVT group had more portal-feces shared genera than the tNPVT group (49 vs. 29). Portal-peripheral-feces shared taxa were predominantly LPS-producing Gram-negative bacteria such as Escherichia-Shigella and Klebsiella. (5) Most bacterial genera in the portal vein showed significant positive correlations with LPS and FVIII in the portal vein. Genera such as Faecalibacterium, Eubacterium_hallii_group, Ruminococcus, Agathobacter, Bacteroides, and Romboutsia were significantly negatively correlated with Child-Pugh scores. Faecalibacterium, Eubacterium_hallii_group, Alistipes, Ruminococcus, Agathobacter, Bacteroides, Blautia, and Subdoligranulum were significantly negatively correlated with MELD scores. Ruminococcus and Agathobacter were significantly negatively correlated with D-Dimer, while Subdoligranulum showed significant positive correlations with LPS and FVIII in the portal vein.ConclusionIntestinal dysbiosis and translocation in cirrhotic patients with PVT lead to differential changes in the portal and peripheral circulatory microbiomes. This may contribute to the formation of PVT by inducing endotoxemia and systemic inflammation, providing a new microbiological perspective on the pathogenesis of cirrhosis-related PVT through the gut-liver axis.